T Helper 1 and T Helper 2 Cytokines in Atopic Children With Steroid-sensitive Nephrotic Syndrome (Iranian Journal of Kidney Diseases, 2015)
Introduction. A higher incidence of allergic disorders has been documented in children with steroid-sensitive nephrotic syndrome (SSNS); however, the role of cytokines associated with T helper 1 and T helper 2 cells is not fully elucidated. This study aimed to evaluate the role of T helper 1 and T helper 2 cytokines in both remission and activity phases among atopic versus nonatopic children with SSNS. Materials and Methods. Fifty-two children with SSNS (21 with atopic disorders and 31 nonatopics) and 60 healthy children were enrolled in the study. The healthy controls were comparable with the patients in terms of age and sex distribution. Serum levels of immunoglobulin E (IgE), interleukin (IL)-2, tumor necrosis factor (TNF)-α, IL-4, and IL-13 were measured in activity and remission phases of the disease and in controls. Results. Serum levels of IgE, TNF-α, IL-4, and IL-13 were significantly increased in the children with SSNS during the active compared to remission phase and the controls. T helper 2 markers (IgE, IL-4, and IL-13) were also higher in the atopic patients with SSNS than those without atopy. No significant difference was observed in IL-2 levels between the SSNS children in activity and remission phases and the controls, or between atopic and nonatopic children with SSNS in activity and remission phases. Conclusions. Our findings suggested that type 2 immune response prevailed during the active stage in children with SSNS, atopic or not, with persistent elevation of IgE during remission. T helper 2 imbalance was markedly exaggerated in atopic children.